Classification of Digital Objects as Virtual Property and Legal Qualification - Kadys, Eimantas (Teisė, 2024)
The main objective of this article is to examine and assess which digital objects can be classified as virtual property and how they should be qualified under Lithuanian positive law. In this context, the subject of this article is the classification of digital objects as virtual property, and their legal status. In order to achieve its objective, the article first analyses the characteristics that digital objects in virtual space must possess in order to be classified as virtual property. This objective establishes that in order for a particular digital object to qualify as a virtual property object, the computer code, in which the digital object is expressed, must satisfy the characteristics of competitiveness, permanence and interconnectedness. The second objective of the article is to identify the legal status of virtual property objects in foreign legal systems. This objective is achieved by establishing that some foreign countries recognise ownership of these digital objects directly under their positive domestic law. This recognition of the property status of these digital objects reflects the modern social reality of the digital age and avoids the legal disputes that often arise in states where there is no clear legal status of virtual objects under positive law. The third objective of the article is to assess how virtual property objects should be qualified in Lithuania – by classifying them as sui generis and creating a separate legal regime, or by qualifying them as res incorporales objects. This task leads to the conclusion that virtual property objects can be classified as res incorporales objects and qualified as objects of property law under Lithuanian civil property law.
Keywords: digital objects; virtual property; object of property law; res incorporales; sui generis